Evaluation of the Effectiveness of Micro-Osteoperforation in Reducing the Time Required to Treat Crowding of Lower Incisors Treated with Clear Aligners (Journal of Hama University, 2025)
The research aims to evaluate the effectiveness of micro-osteoperforation in reducing the time required to treat crowded lower incisors (without extraction) treated with clear aligners. The research sample consisted of (40) patients with a mean age of (22.3±1.3) years. They were randomly distributed either to the micro-osteoperforation group or to the control group with an allocation ratio of (1:1). The lower incisors of patients in both groups were decrowded with clear aligners, and before applying the first clear aligner to patients in the micro-osteoperforation group, 14 cortical perforations were made, two perforations in each interdental space of the lower incisors from the buccal aspect. The diameter of each perforation was 1.2 mm, and its depth was 1 mm within the cortical bone using a lance drill after making adjustments to it. The time required for treatment was evaluated by calculating the number of days between times T0 and T1 for patients in both groups. Where: T0: is the time for applying the first clear aligner (initiate the assumed treatment plan, which is to align the crowded lower incisors without extraction), and T1: is the time for removing the last clear aligner (the end of the assumed treatment plan, when the last clear aligner is neutral). The results of the study showed that there was a statistically significant difference between the two groups regarding the time required to treat crowded lower incisors treated with clear aligners (P-value < 0.05), and the arithmetic average of the time required for treatment in the studied group was 62 days less than that in the control group. Micro-osteoperforation is considered an effective surgical procedure in reducing the time required to treat crowded lower incisors (without extraction) treated with clear aligners, as it shortened the time required to achieve this by 47.69% compared to the control group (treated with clear aligners only).
Keywords: Micro-osteoperforation, Clear aligners, Crowding of the lower incisors